Patient‐reported ability to walk 4 m and to wash: New clinical endpoints and predictors of survival in patients with pre‐terminal cancer - Markus S. Anker; Alessia Lena; Eric J. Roeland; Jan Porthun; Sebastian Schmitz; Sara Hadzibegovic; Philipp Sikorski; Ursula Wilkenshoff; Ann‐Kathrin Fröhlich; Luisa Valentina Ramer; Matthias Rose; Jan Eucker; et al. (Wiley, 2023)
Abstract Background Maintaining the ability to perform self‐care is a critical goal in patients with cancer. We assessed whether the patient‐reported ability to walk 4 m and wash oneself predict survival in patients with pre‐terminal cancer. Methods We performed a prospective observational study on 169 consecutive hospitalized patients with cancer (52% female, 64 ± 12 years) and an estimated 1-12 months prognosis at an academic, inpatient palliative care unit. Patients answered functional questions for 'today', 'last week', and 'last month', performed patient‐reported outcomes (PROs), and physical function assessments. Results Ninety‐two (54%) patients reported the ability to independently walk 4 m and 100 (59%) to wash 'today'. The median number of days patients reported the ability to walk 4 m and wash were 6 (IQR 0-7) and 7 (0-7) days ('last week'); and 27 (5-30) and 26 (10-30) days ('last month'). In the last week, 32% of patients were unable to walk 4 m on every day and 10% could walk on 1-3 days; 30% were unable to wash on every day and 10% could wash on 1-3 days. In the last months, 14% of patients were unable to walk 4 m on every day and 10% could only walk on 1-10 days; 12% were unable to wash on every day and 11% could wash on 1-10 days. In patients who could walk 'today' average 4 m gait speed was 0.78 ± 0.28 m/s. Patients who reported impaired walking and washing experienced more symptoms (dyspnoea, exertion, and oedema) and decreased physical function (higher Eastern Cooperative Oncology Group Performance Status, and lower Karnofsky Performance Status and hand‐grip strength [unable vs. able to walk 'today': 205 ± 87 vs. 252 ± 78 Newton, P = 0.001; unable vs. able to wash 'today': 204 ± 86 vs. 250 ± 80 Newton, P = 0.001]). During the 27 months of observation, 152 (90%) patients died (median survival 46 days). In multivariable Cox proportional hazards regression analyses, all tested parameters were independent predictors of survival: walking 4 m 'today' (HR 0.63, P = 0.015), 'last week' (per 1 day: HR 0.93, P = 0.011), 'last month' (per 1 day: HR 0.98, P = 0.012), 4 m gait speed (per 1 m/s: HR 0.45, P = 0.002), and washing 'today' (HR 0.67, P = 0.024), 'last week (per 1 day HR 0.94, p=0.019), and 'last month' (per 1 day HR 0.99, P = 0.040). Patients unable to walk and wash experienced the shortest survival and most reduced functional status. Conclusions In patients with pre‐terminal cancer, the self‐reported ability to walk 4 m and wash were independent predictors of survival and associated with decreased functional status.